El Sintesista: Contexto, Evolución y Nuevas Perspectivas de Desarrollo (2010)
After a historical review of the synthesizer´s evolution and the study of cognitive approaches of musical teaching, some factors are stated and defined that are important to consider for the design and construction of new instruments and audio synthesis interfaces. Multidimensionality, timbre spaces, multi sensorial feedback and expressiveness appear as decisive aspects in the construction of synthesizers, shaping the paradigm to be followed by the new generation of digital instrument designers. Their main challenge is to develop more intuitive and stimulating tools that ease the approaching process of musicians to sound synthesis.